Discourse on the Legality of Rebellion in the Manuals of Creed with Focus on the Ḥanafī and Shāfi‘ī Jurists - Tabassum, Sadia (Islamic Studies, 2020)
The present paper digs out the manuals of creed written by eminent jurists of the Ḥanafī and Shāfi‘ī schools of law so as to expound the position of Islamic law on the issue of resistance against unjust rulers and usurpers. The reason for this is that discussions on this issue are found in the works on creed (called al-fiqh al-akbar), not in the books of law-proper (fiqh). These discussions revolve around the concepts of prohibition of mischief and disorder, the obligation of commanding good and forbidding evil, and choosing the lesser of the two evils. Abū Ḥanīfah, the founder of the Ḥanafī school of law, held that an unjust person or the one who committed major sins was not entitled to rule the Muslim community. However, he did not allow the attempt to forcibly remove such a ruler as that might lead to bloodshed and disorder, unless it could be proved that it was the lesser of the two evils. Moreover, he was of the view that all the lawful commands of such an unjust ruler must be obeyed until he remained in power. Thus, while denying legitimacy to an unjust ruler, Abū Ḥanīfah accepted the consequences of the de facto authority for such a ruler under the doctrine of necessity. The paper shows that the same approach was later adopted by the Shāfi‘ī jurists Imām al-Ḥaramayn al-Juwaynī and his illustrious disciple Abū Ḥāmid al-Ghazālī. The paper also disproves the theory preached by some contemporary scholars that al-Juwaynī and al-Ghazālī accepted the validity of two caliphs at one time. It shows that they meant administrators (umarā’, sing. amīr), not caliphs and that they emphatically asserted the need of having one caliph for the whole Muslim ummah.